До питання територіальних меж земель Чернігівської козацької хоругви (1625-1648 рр.). (Zaporizhzhia Historical Review, 2021)
The research explores the process of forming the network of settlements in the lands of Chernigivska cossack gonfalon (khorugv) that later had been included into the Royska sotnia (company) of Chernigiv regiment. The author presisely defines the borders of this territory colonized by the Cossacks.